The contemporary condition - Cox, Geoff; Lund, Jacob (Sternberg Press, 2016)
The aim of the Contemporary Condition book series is to question the formation of subjectivity and concept of temporality in the world now. It begins from the assumption that art, with its ability to investigate the present and make meaning from it, can lead to an understanding of wider developments within culture and society. Addressing a perceived gap in existing literature on the subject, the series focuses on three broad strands: the issue of temporality, the role of contemporary media and computational technologies, and how artistic practice makes epistemic claims